Peripancreatic abscess supported by Bordetella hinzii. (March 2020) - Kampmeier, S.; Rennebaum, F.; Schmidt, H.; Riegel, A.; Herrmann, M.; Schaumburg, F.
Abstract: We report a novel case of an infection with Bordetella hinzii, a pathogen usually detected in poultry, supporting a peripancreatic abscess formation as a complication of an acute necrotizing pancreatitis.